Adsorption Equilibria of an Insecticide Diazinon onto Natural Clay - Mohammad S El-Geundi; Assanousi A. Abufares (مجلة المختار للعلوم, 2013)
Adsorption isotherm has been investigated for the adsorption of diazinon onto natural clay. The influence of particle size range of natural clay on the adsorption capacity has been studied with three different ranges. The results showed that the adsorption capacity of the natural clay increased from 4.9 mg/g (65.5% removal) to 6.1 mg/g (81.0% removal) for decreasing the particle diameter from 500-710 μm to 250-355 μm. The experimental results have been fitted with the Langmuir, Freundlich and Redlich-Peterson models. It is clear from the results that the Freundlich model fits the experimental data significantly better than the Langmuir and Redlich-Peterson models.